Canonical Wnt signaling protects hippocampal neurons from Aβ oligomers: role of non-canonical Wnt-5a/Ca2+ in mitochondrial dynamics - Silva-Alvarez, Carmen; Arrazola, Macarena; Godoy, Juan A.; Ordenes, Daniela; Inestrosa, Nibaldo C. (Frontiers in Cellular Neuroscience, 2013)
Alzheimer´s disease (AD) is the most common type of age-related dementia. The disease is characterized by a progressive loss of cognitive abilities, severe neurodegeneration, synaptic loss and mitochondrial dysfunction. The Wnt signaling pathway participates in the development of the central nervous system and growing evidence indicates that Wnts also regulate the function of the adult nervous system. We report here, that indirect activation of canonical Wnt/β-catenin signaling using Bromoindirubin-30-Oxime (6-BIO), an inhibitor of glycogen synthase kinase-3β, protects hippocampal neurons from amyloid-β (Aβ) oligomers with the concomitant blockade of neuronal apoptosis. More importantly, activation with Wnt-5a, a non-canonical Wnt ligand, results in the modulation of mitochondrial dynamics, prevents changes induced by Aβ oligomers in mitochondrial fission-fusion dynamics and modulates Bcl-2 increases induced by oligomers. The canonical Wnt-3a ligand neither the secreted Frizzled-Related Protein (sFRP), a Wnt scavenger, did not prevent these effects. In contrast, some of the Aβ oligomer effects were blocked by Ryanodine. We conclude that canonical Wnt/β-catenin signaling controls neuronal survival, and that non-canonical Wnt/Ca2+ signaling controls mitochondrial dysfunction. To our knowledge, this is the first report showing that activation of non-canonical Wnt-5a/Ca2+signaling prevents Aβ oligomer neurotoxicity. Since mitochondrial dysfunction is present in neurodegenerative diseases, the therapeutic possibilities of the activation of Wnt signaling are evident.